Macroscopic angioarchitecture of the utero- fetoplacental complex in alpacas (Vicugna pacos) - Pacheco-Curie, Joel Ivan (2023)
The aim of this study was to describe the arterial supply of the uterine-fetoplacental complex in alpacas during gestation. In total, 26 female alpacas were used; of these, 5 non-pregnant females were used to describe the irrigation of the reproductive tract and the origins of its irrigation; and 21 pregnant females were distributed in subgroups of 7 and slaughtered when they reached the 1st, 2nd and 3rd third of gestation, respectively. The specimens were processed using the filling-corrosion technique. Observation of uterine irrigation in pregnant and non-gravid uteri shows that it originates from the abdominal aorta artery, from where the ovarian arteries emerge, which pass towards the ovaries and from where they continue through the cranial uterine arteries and enter the uterine horns where they anastomose with the lateral and ventral branches of the caudal uterine arteries that take their origin from the iliac arteries. From the lateral branches of the uterine arteries, the spiral arteries that irrigate the uterine horns emerge, the same ones that are found in greater numbers in the left horn and that in pregnant females are observed stretched. The medial branch of the right caudal uterine artery passes into the left horn, thereby increasing the blood supply to that horn. In the placenta, many small vessels form that come together to enter the fetus through the umbilical veins, which anastomose to form the sinus venosus, which pours blood into the hepatic sinusoidal capillaries in a large branch, which then pours into three medium vessels that when joined, emerge from the posterior part of the liver and join to the posterior vena cava, through the so-called ductus venosus, this pours the blood into the right atrium, from where the blood goes to the left atrium through the foramen ovale, then towards the left ventricle from where the aorta artery emerges, where the ductus arteriosus is found which diverts part of this blood towards the pulmonary trunk. The aortic artery continues its course caudally and after the bifurcation of the iliac arteries, the two umbilical arteries emerge that go towards the placenta. It is proposed to identify them with the name of left and right placental arteries, as well as their satellite veins.